Serum Vitamin D and Immunoglobulin E Levels In Patients With Seasonal Allergic Conjunctivitis - Al-Swailmi, Farhan Khashim; Shah, Syed Imran Ali; Al-Mazaideh, Ghassab Mohammad; Sikandar, Mirza Zeeshan (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Seasonal allergic conjunctivitis (SAC) is a mild but common immunoglobulin E (IgE) mediated ocular allergy. Low serum vitamin D levels have been related to some allergic disorders but such data in the clinical context of SAC are missing. Our study investigated serum IgE and vitamin D levels in SAC patients. MATERIALS AND METHODS: A cross-sectional case-controlled study was conducted at University of Hafr Al-Batin, Saudi Arabia involving patients with established diagnosis of SAC and age[1]matched healthy control subjects. Standard patient evaluation of eye dryness (SPEED) questionnaire was scored for the frequency and severity of symptoms. Blood samples were taken to quantify serum IgE and vitamin D levels. Mean +- SD were calculated and independent sample t-test was applied for comparison between groups. RESULT: A total of 52 subjects were recruited into the study in which 26 subjects were patients aged between 20-60 years with an established diagnosis of SAC and another 26 subjects were age-matched healthy controls without any allergy. Mean serum IgE, vitamin D level and SPEED scores were significantly higher in SAC patients than in healthy control (2181.09 IU/ml +- 1062.33 vs 54.83 IU/ml +- 26.67; 38.96 ng/ml +- 11.37 vs. 29.47 ng/ml+- 11.73; 19.42 +- 4.81 vs. 2.19 +- 1.49) with p-value 0.001, 0.005, and 0.001 respectively. Mean vitamin D levels in both groups were within normal range. CONCLUSION: Higher serum vitamin D levels may be linked with SAC, but further research is needed to eliminate irregularities in the existing evidence on the influence of vitamin D in SAC.